Extended Bandwidth Optimized and Energy Efficient Dynamic Source Routing Protocol in Mobile Ad-hoc Networks - Bindiya Bhatia; M. K. Soni; Parul Tomar (Institute of Advanced Engineering and Science, 2018)
With the increase in the evolution of wireless communication, the ad-hoc networks are gaining attention and are significantly becoming the technology solutions to the various problems. Mobile ad-hoc Networks (MANETs) are envisaged to grow as a main component in the today 4G architecture, and ad hoc networks are projected to be a significant element of the whole future wireless communication. The MANETs are infrastructure less, self-forming and self-organizing network in which there is no control of any centralized entity. The nodes are free to move around the network with dynamic topology. But this self formation, flexibility and scalability create many challenges and design constraints like hidden terminal, limited bandwidth, limited energy of a node, unpredictable change in the topology etc. Bandwidth and energy are the scarce resources of the network. In order to effectively manage the consumption of bandwidth and energy, an algorithm is proposed which is the extension of traditional Dynamic Source Routing (DSR) reactive routing protocol. The extended protocol applies the mobile agents to carry the data. The proposed work is intended to optimize the bandwidth and making the protocol energy efficient.